Can Afghanistan be rescued? - Sahibuddin, Wahabuddin (Middle East Forum, 2012)
U.S. president Barack Obama entered office with a bold plan to combat Afghanistan's escalating insurgency, empower its government, encourage a political resolution of the conflict, and secure the cooperation of neighboring Pakistan—all in time for U.S. troops to withdraw by the end of 2014.